State of the Climate of the Central Great Plains - Feddema, Johannes (Kansas State University, 2012)
Extreme weather in much of the U.S. this summer had focused attention on climate change. The Central Great Plains region bridges two of the U.S. climate regions as defined by the National Climatic Data Center, West North Central and South. In both regions the long term trend is towards greater annual precipitation and higher temperatures although these trends vary by season between the two regions. Temperatures have also been rising around the globe with the majority of temperature anomalies being increases from previous averages. Within the U.S. the impact of climate change has been masked by a “warming hole” encompassing much of the nation. The extensive use of irrigation in much of the Great Plains has resulted in cooler maximum and minimum temperatures over much of the region. On a global scale, warmer temperatures are evidenced by a reduction in the area, thickness, and volume of Artic sea ice. Recent changes in the USDA hardiness zone map as well as phonological indicators point towards a general warming trend.
Keywords: Climate change; Temperature anomalies; Great Plains; Climatology